SACRED MYTHS OF THE CEREKANG INDIGENOUS COMMUNITY: LOCAL WISDOM STRATEGIES FOR ENVIRONMENTAL PRESERVATION - Hadrawi, Muhlis; Sherira, Sherira; Bachrong, Faizal; Agus, Nuraidar; Yusuf, Yusuf; Syamsuriah, Syamsuriah; binti Daeng Jamal , Daeng Haliza (Al-Qalam, 2025)
This article examines the sacred myths upheld by the Cerekang Indigenous Community, conceptualized through ideas of "prohibition" and "necessity" regarding actions in specific natural locations. These myths function not only as local normative systems but also as expressions of ecological wisdom that guide the community in protecting the natural environment from damage. The Cerekang community continues to preserve these ancestral beliefs, which are deeply integrated into their cultural identity and daily practices. A descriptive-qualitative method was employed to explore the traditional myths in the Cerekang Customary Area, Malili District, East Luwu Regency. Data were collected through direct observation and interviews with local community members, and then analyzed by drawing connections with literary references, particularly I La Galigo volume 1 (ms NBG 188), featuring Batara Guru as the central figure. Findings reveal that the core of the myth centers on Pengsimaoni Hill, believed to be the site where Batara Guru descended from the upper world (botillangi). This sacred narrative forms the basis for protecting ten natural toponyms within the Cerekang area. These toponyms, each linked to Batara Guru’s journey, shape local norms that define what is allowed and prohibited in daily conduct. The myths serve as moral guidelines, fostering respect for nature and reinforcing social cohesion. By embedding ecological values in cultural narratives, the myths act as a local wisdom system that protects the environment and uphold communal identity. In essence, these sacred myths reflect a deeply rooted environmental ethic that continues to guide the lives of the Cerekang people.